Exploring institutional reform of Korean civil service pension: Advocacy coalition framework, policy knowledge and social innovation - Keunyoung Lee; Kwangho Jung (Journal of Open Innovation: Technology, Market, and Complexity, 2018)
This paper examines what factors are associated with the 2015 pension reform of Korean civil servant as social innovation. We explore what lessons we can learn from the pension reform in terms of the Advocacy Coalition Framework (ACF) model. The ACF model allows us to identify how the substantial reform is, relying on policy knowledge and entrepreneurs, possible in terms of political and social consensus. It also clearly demonstrates the possibility of systematic pension reform at an appropriate level through social learning and policy learning. Through the ACF model, we review how South Korea's civil servant pension reform act occurred at the end of May 2015. The temporal scope covers from 2009 latest reform, and the 2014's President administrative policy speech that had strongly been showed her will to reform the pension issue to the end of May 2015 when the reform bill enacted. We investigate each advocacy coalition in order to elucidate the actors that constitute the two coalition groups and to scrutinize whether a policy broker had existed in the process. We also attempt to find the relatively stable parameters and external events that affected the reform and also the belief system that shared by two advocacy coalition group. The result clearly shows that the two coalition groups shared their normative beliefs ultimately, for example, the need to change the current civil servant's pension system, but, the gap in the numerical change in the policy core belief and secondary belief between the two actors had seemed to be excessively large and uncompromising. A policy broker who can coordinate the interests and interests of stakeholder groups over the government pension reform proposal was desperately needed. Negotiation and leadership of the policy entrepreneurs led to a settlement of the government pension reform proposal at the end of May 2015. Their entrepreneurial activities led to an appropriate level of social consensus on the sustainable reform of pension system through policy knowledge and learning. Further research is required to explore how models of socially innovative forms of governance are created in various pension reforms across various countries. It is also required to examine how policy entrepreneurs use policy knowledge and information for a successful institutional reform through social innovation across various countries.
Keywords: 650